Giant, Bleeding, and Ulcerating Proliferating Trichilemmal Cyst, With Delayed Treatment Due to Coronavirus Outbreak: A Case Report and Review of the Literature - Kiel, Cecilie Mullerup; Homøe, Preben (Frontiers in Surgery, 2021)
We report a case of a large, ulcerating proliferating trichilemmal cyst in a 76-year-old woman, with clinical, radiological, macroscopic, and microscopic correlation. The outbreak of the Coronavirus pandemic delayed her treatment. We review the literature on proliferating trichilemmal cysts, which are relatively rare tumors, which generally are considered benign. However, we found a high rate of malign cases, which stresses the importance of rapid surgical excision and histological diagnosis. Even though our proband had delayed treatment, the tumor did not transform to a malignant form.